2015
DOI: 10.1002/chem.201503921
|View full text |Cite
|
Sign up to set email alerts
|

Direct Catalytic Asymmetric Mannich‐Type Reaction of α‐N3 Amide

Abstract: An α-N3 7-azaindoline amide serves as a latent enolate to directly engage in an asymmetric Mannich-type reaction with N-thiophosphinoyl imines by the action of a cooperative catalyst. The thus-obtained highly enantioenriched anti-adduct was transformed into β-amino-α-azido acid in high yield by simple acidic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…[15a] More recently, Kumagai and Shibasaki have developed direct and asymmetric aldol and Mannich reactions from α‐azido 7‐azaindolinylamide catalyzed by a copper(I) complex. [6a], In turn, we have reported that chiral α‐azidoacetyl thiazolidinethiones also participate in direct and stereoselective Lewis acid‐mediated reactions with acetals catalyzed by nickel(II) complexes . All together, these examples indicate that certain metal enolates of α‐azido carboxylic compounds are stable enough to engage in the stereoselective construction of carbon–carbon bonds.…”
Section: Resultsmentioning
confidence: 97%
“…[15a] More recently, Kumagai and Shibasaki have developed direct and asymmetric aldol and Mannich reactions from α‐azido 7‐azaindolinylamide catalyzed by a copper(I) complex. [6a], In turn, we have reported that chiral α‐azidoacetyl thiazolidinethiones also participate in direct and stereoselective Lewis acid‐mediated reactions with acetals catalyzed by nickel(II) complexes . All together, these examples indicate that certain metal enolates of α‐azido carboxylic compounds are stable enough to engage in the stereoselective construction of carbon–carbon bonds.…”
Section: Resultsmentioning
confidence: 97%
“…Although methyl ketones are readily deprotonated with these catalysts, the enolization of less acidic ketones, esters, amides, and thioesters typically requires further activation of these substrates by the installation of electron‐withdrawing substituents (e.g. OH, NCS, SMe, CF 3 ,, N 3 , F,).…”
Section: Methodsmentioning
confidence: 99%
“…Given the variety of different catalysis protocols to achieve asymmetric Mannich type reactions, [ 69 ] this methodology is without doubt one of the most versatile strategies to access the α,β‐diamino acid scaffold from simple starting materials. [ 7,70–85 ]…”
Section: β‐Amino Acid Derivativesmentioning
confidence: 99%
“…Using simple Cu‐sources in combination with ligand L13 they were able to access amides 150 by reacting aldimines 57 with α‐azido‐azaindoline 149 with excellent selectivities (Scheme 31A). [ 70 ] After acidic hydrolysis, the obtained anti ‐configured β‐amino‐α‐azido products were then converted straightforwardly to the corresponding diamino acids 151 by reduction of the azido group under Pd‐catalysis. On the other hand, syn ‐diamino esters 153 were synthesized successfully by He's and Zhang's research groups very recently (Scheme 31B).…”
Section: β‐Amino Acid Derivativesmentioning
confidence: 99%